2012
DOI: 10.1371/journal.pone.0049227
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ Protein GIPC Regulates Trafficking of the LPA1 Receptor from APPL Signaling Endosomes and Attenuates the Cell’s Response to LPA

Abstract: Lysophosphatidic acid (LPA) mediates diverse cellular responses through the activation of at least six LPA receptors – LPA1–6, but the interacting proteins and signaling pathways that mediate the specificity of these receptors are largely unknown. We noticed that LPA1 contains a PDZ binding motif (SVV) identical to that present in two other proteins that interact with the PDZ protein GIPC. GIPC is involved in endocytic trafficking of several receptors including TrkA, VEGFR2, lutropin and dopamine D2 receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Interestingly, LARG has previously been linked to signalling from GPCRs such as the lysophosphatidic acid receptor (LPAR1), that is also trafficked by GIPC1 and MYO6 through APPL1 endosomes (Figs 4A and B, and EV3A) 31, 32, 33. We therefore determined whether the MYO6‐GIPC1‐LARG‐SH3BP4 complex links LARG and RHO‐dependent actin organisation to GIPC1 endosome function and position.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, LARG has previously been linked to signalling from GPCRs such as the lysophosphatidic acid receptor (LPAR1), that is also trafficked by GIPC1 and MYO6 through APPL1 endosomes (Figs 4A and B, and EV3A) 31, 32, 33. We therefore determined whether the MYO6‐GIPC1‐LARG‐SH3BP4 complex links LARG and RHO‐dependent actin organisation to GIPC1 endosome function and position.…”
Section: Resultsmentioning
confidence: 98%
“…During development, expression of Lpar2 is more diffuse than Lpar1, although it is clearly present in the embryonic pathways are being uncovered. Toward elucidating these interactions, one study demonstrated that LPA 1 (but not other tested LPA receptors) is traffi cked to early endosomes through a PDZ-mediated motif that facilitates its binding to GAIP interacting protein, C-terminus (GIPC), which attenuates LPA-mediated Akt signaling from adaptor protein containing PH domain (APPL) signaling endosomes (109). Other studies identifi ed LPA as a critical regulator of the Hippo-Yes-associated protein (YAP) pathway, which controls LPA-induced gene expression, cell migration, and cell proliferation.…”
Section: Lpa Receptorsmentioning
confidence: 99%
“…Furthermore, GIPC expression suppresses dopamine 3 receptor Ga i -coupling and prevents dopamine 3 receptor degradation (Jeanneteau et al, 2004). GIPC also plays a role in regulating both the human luteinizing hormone receptor and LPA 1 R trafficking (Hirakawa et al, 2003;Varsano et al, 2012). The interaction of GIPC with LPA 1 R is essential for LPA 1 R trafficking from APPL-positive signaling endosomes to early endosome antigen 1-positive early endosomes (Varsano et al, 2012).…”
Section: Pdz Proteins That Regulate Golgi Traffickingmentioning
confidence: 99%
“…GIPC also plays a role in regulating both the human luteinizing hormone receptor and LPA 1 R trafficking (Hirakawa et al, 2003;Varsano et al, 2012). The interaction of GIPC with LPA 1 R is essential for LPA 1 R trafficking from APPL-positive signaling endosomes to early endosome antigen 1-positive early endosomes (Varsano et al, 2012). Additionally, GIPC links LPA 1 R to the protein kinase B signaling pathway, cell proliferation, and cell motility (Varsano et al, 2012).…”
Section: Pdz Proteins That Regulate Golgi Traffickingmentioning
confidence: 99%
See 1 more Smart Citation